Trajectory of psychological distress and influencing factors in patients with gynecological cancers: a longitudinal study - Li, Feifei; Xu, Jing; He, Yueyuan; Zhang, Shanhong (Frontiers in Oncology, 2024)
ObjectiveTo explore the dynamic changes of psychological distress among patients with gynecological cancers across their treatment journey and identify the characteristics of subgroups of patients with distinct trajectories.MethodsThis study included a convenience sample of 132 patients with cervical cancer, ovarian cancer or endometrial cancer who received surgery and adjuvant chemotherapy in the gynecological department of a Grade III and Class A general hospital in Liaoning Province between November 2022 and October 2023. Patients’ mean age was 55.46 ± 11.12 years. Psychological distress was measured with the Distress Thermometer and Problem List 1 day before surgery, before the first chemotherapy session, at the third chemotherapy session, and at the end of the last chemotherapy session. A latent class growth model (LCGM) was used to identify trajectories of psychological distress and explore influencing factors.ResultsThe LCGM identified three different trajectories of psychological distress in patients with gynecological cancers, including Class 1, “high level decline “ (37.4%), Class 2, “no psychological distress” (24.1%), and Class 3, “high level stable” (38.5%). Multinomial logistic regression analysis showed monthly per capita household income, disease type, positive coping style and temperament type were significant predictors of trajectory of psychological distress in patients with gynecological cancers.ConclusionsThis study showed heterogeneity in the trajectory of psychological distress among patients with gynecological cancers. These findings should raise awareness among healthcare providers of the need to implement screening measures and timely psychological interventions in this patient population.